Interactions of Antimicrobial Peptides with Bacterial Membranes and Membrane Components - Malmsten, Martin (Current Topics in Medicinal Chemistry, 2016)
Antimicrobial peptides (AMPs) have attracted considerable recent interest as potential therapeutics, motivated by increasing resistance development against conventional antibiotics. This brief overview summarizes some key aspects related to the interaction of AMPs with bacterial and cell membranes, as well as with membrane components, which is at the core of the mode-of-action of these compounds. Throughout, studies on peptide interactions with model lipid membranes and membrane components are correlated to biological results on antimicrobial and anti-inflammatory effects of AMPs, and translated into therapeutic considerations.
Keywords: AMP